Recent Developments in Solvent and Salt Effects on Ene Reactions of Singlet Oxygen - J. Kinart, Wojciech; M. Kinart, Cezary; Sendecki, Marcin (Current Organic Synthesis, 2013)
The synthetic potential of the photo-oxygenation has been discussed. It provides an exquisite regioselective, and in many cases stereoselective, entry into synthetically useful feedstock using an environmentally benign oxidant. Allyl hydroperoxides are the principal products when unsaturated compounds undergo photo-oxidation. The singlet oxygen ene reaction is bimolecular process with a rate that depends on concentration of both the substrate and singlet oxygen. Convenient rates are achievable in many common organic solvents using photosensitization. However, condensed phase photo-oxidation conditions suffer from several drawbacks. Therefore, the area of polymer-supported catalysis has been extensively studied. The singlet oxygen ene reaction of allylic stannanes leads to formation of Mene, H-ene and cycloaddition products. Its relative yields depend on structural and environmental conditions. The considerable efforts have been made to optimize the selection of the ideal solvent to carry the photo-oxidation. It has been observed that in the presence of different salts such as LiClO4 reaction rates are considerably faster. Noticed effects depend on the concentration of the salt and vary with change of the solvent. Results of photo-oxidation of phenols indicate that yield of the reaction and type of products dependz on pH of studied solution and the addition of LiClO4, CF3SO3Li or Bu4NF which catalyze this reaction. The catalytic effect of LiClO4 on reactions of singlet oxygen with different olefins and allyltin compounds has been explained as a result of stabilization of the transition state by the ionic medium. It also occurs that physicochemical properties of organic solvents and effects joined with solvation by them LiClO4 are responsible for this catalysis.
Keywords: sensitizers